2021
DOI: 10.1016/j.ijsolstr.2021.111047
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of mesoporous amorphous NiTi alloy to external deformations

Abstract: The porous titanium nickelide is very popular in various industries due to unique combination of physical and mechanical properties such as shape memory effect, high corrosion resistance, and biocompatibility. The non-equilibrium molecular dynamics simulation was applied to study the influence of porosity degree on mechanical properties of porous amorphous titanium nickelide at uniaxial tension, uniaxial compression, and uniform shear. We have found that the porous amorphous alloy is characterized by a relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The same conclusion was reported by Galimzyanov and Mokshin [46], who carried out a computational study to investigate the effect of porosity on the mechanical properties of NiTi alloys. Through shear, tensile, and compression tests, it can be concluded that the increasing porosity of NiTi alloys causes a decrease in the modulus of elasticity and strength of the NiTi alloy [46]. Similar studies may need to be carried out on TiAl alloys to inspire potential wider applications in the future.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The same conclusion was reported by Galimzyanov and Mokshin [46], who carried out a computational study to investigate the effect of porosity on the mechanical properties of NiTi alloys. Through shear, tensile, and compression tests, it can be concluded that the increasing porosity of NiTi alloys causes a decrease in the modulus of elasticity and strength of the NiTi alloy [46]. Similar studies may need to be carried out on TiAl alloys to inspire potential wider applications in the future.…”
Section: Discussionsupporting
confidence: 75%
“…However, they are stiffer under tensile loading than under compression. In the case of compressive testing for systems with porosity, the compressive strength decreases in materials with greater porosity, as was the result of a previous study by Xu et al [45] and Galimzyanov and Mokshin [46] for the NiTi alloy system. [21]; c from ref.…”
Section: Stress-strain Relationsupporting
confidence: 53%
See 2 more Smart Citations
“…Figure 1 (see inset) shows the T-dependence of the fraction of liquid phase atoms with respect to the atoms of the entire system. The form of this dependence is typical for activation-type processes, such as the crystal nucleation and the formation of liquid droplets in saturated vapor [17][18][19][20], and this dependence is well reproduced by the exponential expression of the following form…”
Section: Simulation Procedures and Resultsmentioning
confidence: 86%